Determinants of regional variations in the rate ofl profit. An empirical analysis for Austrian manufacturing 1972-1992 - Christian Rammer (European Regional Science Association (ERSA), 1998)
The rate of profit represents a central concept in economics and is commonly seen as one of the most accurate indicators for economic vitality of firms, industries, and regions. The level of profit rates is supposed to guide investment shifts between sectors and over space, the speed and direction of technological change, and the development of economic activity in the long run. Differentiales in regional profit rates may therefore be a major source for differences in regional economic development and regional competitiveness. While neoclassical regional economic theory postulates a tendency towards an equalisation in regional rates of profit, empirical studies show considerable and persistent regional differences in profitability. The aim of the paper is to analyse the pattern of profitability over time and space for Austrian manufacturing on a highly disaggregated regional level for the time period 1972-1992. An eclectic model is employed in order to analyse major sources for regional variations in profit rates. The model distinguishes four groups of determinants: production technology, capital-labour-relations, market competition, and spatial variables such as transport costs and agglomeration economies.
Keywords: 330